El uso de las redes sociales y la salud mental en los jóvenes - Sellan Oquendo, Genesis Natacha (2025)
This research is entitled the use of social networks and mental health in young people in the Babahoyo canton in the year 2024-2025, which originates because social networks, unquestionably, are resources on a global scale, public and private, which enable communication between two or more people, exceeding physical proximity. From that perspective, it could be considered that the repeated and abusive use of digital conditions can lead to a habit and little by little a dependency and, over time, it will become a more serious problem, where without foreseeing it, it will be a more serious inconvenience. Therefore, the objective of the research is to determine the impact of social networks on the mental health of young people. To accomplish this, a non-experimental cross-sectional methodological design was used with a descriptive scope with a mixed approach under the inductive method complemented by techniques such as observation and survey, having as results that the excessive use of social networks in the Babahoyo canton affects the mental health of young people.